Entre moralizados e civilizados: indígenas e portugueses no Brasil através da obra de Wilhelm Ludwig Karl Von Eschwege (1810-1821) - Bartholomeu, Dante Hesse (2017)
This research aims to understand how German traveler Wilhelm Ludwig Karl von Eschwege, the Baron of Eschwege, understands and represent the dichotomy between “civilized” man – the Portuguese and their administration in Brazil – and the native indigenous Brazilian – the “savage” man, which he represents under a rousseaunian perspective – in the first half of the 19th century. Thus, through travel literature, this project establishes the following questioning: to Eschwege, which of the aforementioned agents will stand as civilized and which one will stand as moralized, in a philosophical point of view, given the fact that these nations coexist and relate themselves in the whole of Brazil‟s territory during the years of his stay; between 1810 and 1821. What are the social-political aspects that dialogue through convergences and divergences, when the traveler puts these nations in comparison? This way, in an attempt of showing the indigenous societies and the Portuguese corporation through representations shaped in a specific and delimited universe, there is an effort in understanding and problematizing, based on narratives and experiences described in the journey reports, the means of coexistence and social relations between these agents. This is achieved under the prism of the root source Eschwege, whose reports led to an influence of the European imaginary on the New World